2019
DOI: 10.1074/jbc.ra118.007009
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein L6 (RPL6) is recruited to DNA damage sites in a poly(ADP-ribose) polymerase–dependent manner and regulates the DNA damage response

Abstract: Edited by Patrick SungRibosomal proteins are the building blocks of ribosome biogenesis. Beyond their known participation in ribosome assembly, the ribosome-independent functions of ribosomal proteins are largely unknown. Here, using immunoprecipitation, subcellular fractionation, His-ubiquitin pulldown, and immunofluorescence microscopy assays, along with siRNA-based knockdown approaches, we demonstrate that ribosomal protein L6 (RPL6) directly interacts with histone H2A and is involved in the DNA damage resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Similarly, some RPs have been implicated in processes independent of translation, most notably regulation of p53 degradation (27). Here, we demonstrate that SBDS and RPS19 also have roles in DNA DSB repair.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similarly, some RPs have been implicated in processes independent of translation, most notably regulation of p53 degradation (27). Here, we demonstrate that SBDS and RPS19 also have roles in DNA DSB repair.…”
Section: Discussionsupporting
confidence: 55%
“…Specifically, eIF6 depletion did not rescue the HR defect, as would be expected if ribosome subunit joining was restored ( Figure 3A); EFL1 depletion did not phenocopy the HR defect of SBDS-deficient cells ( Figure 3B), as would be expected if impaired ribosome subunit joining was central to the phenotype; and both SBDS and RPS19 were recruited to sites of an induced DSB ( Figure 9). While the association of these proteins with DSBs is novel, a few other ribosomal proteins, RPL6, RPL8 and RPS14, but not RPL9, have been shown previously to be recruited to sites of DNA damage-induced by laser microirradiation (27). RPL6 recruitment occurs via interaction with H2A and in a PARP-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPL6 was identified as an upregulated gene in multidrug‐resistant gastric cancer cells . Yang et al (2019) found that RPL6 could be recruited to DNA damage sites and regulated the DNA damage response, which suggests its nuclear localization. Then, focusing on RPL6, we confirmed that NSUN2 can directly interact with RPL6.…”
Section: Discussionmentioning
confidence: 99%
“…p53 plays an important role in DNA damage-induced G2/M checkpoint activation and in inhibiting entry into mitosis (Fernandez-Capetillo et al, 2002; Yang et al2018). In our previous report, we established the range of MTX doses that induces DNA breaks in mESCs.…”
Section: Discussionmentioning
confidence: 99%